Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

manny12345

  • 3 years ago

18-6a=4a-4(a-3)

  • This Question is Closed
  1. liza2
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    18-6a=4a-4(a-3) 18-6a=4a-4a+12 -6a= 12-18 -6a= -6 a = 1 Do all of the steps make sense?

  2. manny12345
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    yes, and what kind of problem is this called?

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy